Adult ADHD Diagnosis, Symptoms of Impulsivity, and Emotional Dysregulation in a Clinical Sample of Outpatients Consulting for a Behavioral Addiction. Issue 7 (May 2023) - El Archi, Sarah; Barrault, Servane; Garcia, Manuel; Branger, Stéphanie; Maugé, Damien; Ballon, Nicolas; Brunault, Paul
Objective: This study aimed to investigate ADHD in adult outpatients seeking treatment for a behavioral addiction and to identify the specificity of psychopathological features if the behavioral addiction cooccurs with adult ADHD. Method: Sixty-five outpatients consulting for a behavioral addiction were assessed for ADHD (DIVA-5), addictive disorder (alcohol, tobacco, cannabis, gambling, gaming, food, and sex), impulsivity (UPPS-P), and emotion dysregulation (DERS-36). Results: In our sample of outpatients seeking treatment for a behavioral addiction, adult ADHD was independently associated with higher compulsive sexual behavior disorder severity, "sensation seeking, " "positive urgency, " difficulties in "goal-directed behavior, " "impulse control, " and use of "emotion regulation strategies" in the context of intense emotions. A 29% of the sample was diagnosed for adult ADHD. Conclusion: The association of adult ADHD with specific dimensions of impulsivity and emotion dysregulation, pave the way for future clinical and research perspectives.